MENGANALISIS MODEL PEMBELAJARAN BERDIFERENSIASI UNTUK ANAK BERKEBUTUHAN KHUSUS (ADHD/HIPERAKTIF) BERBAKAT/GIFTED/TALENTED DI SKH ELMYRA SHANUM - Yahdinil Firda Nadhirah; Maurizza Nathania Rahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Differentiated learning views students differently and dynamically, where teachers see learning from various perspectives. Differentiated learning does not mean individualized learning. However, it is more directed at learning that accommodates students' needs through independent learning and maximizes students' learning opportunities. In differentiated learning, teachers must understand and realize that there is not just one way, method, strategy used in learning a lesson material. Teachers need to prepare lesson materials, activities, daily assignments both in class and at home, and final assessments according to students' readiness to learn the lesson material, interests or what students like in learning, and how to deliver lessons that are in accordance with the learning profile of their students